Sosialisasi Dan Pelatihan Marketing E-Commerce Dan Sistem Informasi Akuntansi Untuk Mendukung Usaha Kecil Menengah (UKM) Kerajinan Logam Di Kecamatan Cepogo Boyolali Menghadapi Revolusi Industri 4.0: Sosialisasi Dan Pelatihan Marketing E-Commerce Dan Sistem Informasi Akuntansi Untuk Mendukung Usaha Kecil Menengah (UKM) Kerajinan Logam Di Kecamatan Cepogo Boyolali Menghadapi Revolusi Industri 4.0 - ithri Setya Marwati marwati (Lembaga Penelitian dan Pengabdian Masyarakat, 2022)
MSMEs are the most important pillars in the Indonesian economy. The most famous copper craft center in Indonesia is Tumang Village, Cepogo, Boyolali, Central Java. It is called a craft center because of the local residents, some of whom are copper craftsmen. The problems that occur are the limited information technology and the ability to access technology and information from outside, as well as management that has not been implemented properly that can support the craftsman development program, both from the point of view of the professionalism of its human resources as well as in terms of product development, craft design equipment and management. In addition, sales systems and data processing are still carried out conventionally, resulting in limited marketing opportunities and transaction processing. The lack of literacy of SMEs towards information technology is the cause. Only about 25% of all business actors in Tumang have utilized technology for marketing and financial management. The implementation of this Community Service is intended to provide socialization and training as well as assistance to improve skills and knowledge for craftsmen to market their products on a global scale and provide electronic sales applications for craftsmen so that customers can get information quickly, and can make online shopping transactions. As well as a digital accounting information system that will increasingly provide convenience in creating accountable, transparent, and secure financial reports. This PKM activity was carried out by the Community Service Team (PKM) from the Management Economics Study Program at the Islamic University of Batik Surakarta through the 2021 Matching Fund grant. The PKM activity was aimed at brass and copper metal craftsmen in Tumang, Cepogo Boyolali. The methods used are socialization, training, and mentoring. The results of PKM activities are technological innovations in the form of a Marketplace Application called